FORMULATION AND ANTIOXIDANT ACTIVITY FACE MIST KOMBUCHA OF TELANG FLOWER (Clitoria ternatea L.) WITH DPPH METHOD (2,2 Difenyl-1-Piksryhidrazil) - Yayan Rizikiyan; Sopiah, Sopi Siti; Amelia, Renny; Indriaty, Sulistiorini; Senja, Rima Yulia (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Telang flower (Clitoria ternatea L.) contains anthocyanins that are efficacious as natural antioxidants. Face mist with synthetic materials, such as tertiary-butyl hydroquinone (TBHQ), has side effects that are carcinogenic and can cause tumors if used for a long time. Currently, many studies haveeinvestigated the conventional biotechnology product kombucha,, which is a drink made from tea fermented by bacteria and yeast (Scoby/Symbiotic Colony (Culture) Bacteria &Yeast,), as the initial culture of the tea produces an aroma or sour taste. Kombucha has various anti-inflammatory, antibacterial, and antioxidant activities of certain strains, which are expected to provide good antioxidant activity when combined with the natural ingredients of Telang flowers. In this study, telang flower simplicia was fermented for 6 days until telang flower kombucha tea was obtained, and face mist preparations in three concentrations (5%, 7,5%, and 10%) were prepared to determine the antioxidant activity using the DPPH method measured by UV-Vis spectrophotometry by looking at the % inhibition and IC50 values. Based on the results of the evaluation with the parameters of organoleptic testing, pH, homogeneity, spray dispersion, specific weight, viscosity, and drying time met the requirements. The result of the antioxidant activity test of vitamin C of 4,36 ppm, kombucha of telang flower of 14,19 ppm, and face mist of kombucha of telang flower with concentrations of 5%, 7,5% and 10% produced IC50 values of 21,19 ppm, 19,62 ppm, and 17,52 ppm and were included in the very strong category. Keywords: Antioxidant, Telang flower, Face mist, DPPH, Kombucha